Energy poverty indicators: Conceptual issues. Part I: The ten-percent-rule and double median/mean indicators - Rudolf Schuessler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Energy poverty, long considered a problem limited to developing countries only, is now widely acknowledged as a challenge for advanced OECD countries as well. How energy poverty is perceived depends on the conceptualization and assessment of the underlying phenomena: inappropriately high costs for the provision of adequate energy services and/or a resulting push into poverty. In Europe, the UK has spearheaded the definition and measurement of such phenomena. The most common way to measure energy poverty is to set a 10 percent threshold of energy-related expenditure relative to net income. At the time this indicator was being developed, it equaled double the median share of energy expenditure relative to the income of all residents. This paper discusses approaches to measuring energy poverty and argues that the double median share threshold endorsed by British researchers is ill-suited for determining energy poverty. A fixed percentage threshold may be more suitable, provided it is empirically confirmed, adequately modified, and regularly updated.
urn:nbn:de:bsz:180-madoc-368880
Keywords: I32; 330; energy poverty; indicators; social justice